Reform that deforms: Legislative Decree 1189 and the opportunity to improve the Bankruptcy System - Puelles Olivera, Luis Guillermo (2016)
This article addresses the issue referred to the permanent concern over the debate about adjustment that national bankruptcy systems should have to adapt to the needs of the users, in this case, companies in difficulties, creditors, employeesand others.In the case of Peru, the author indicates the analysis of the benefits of the reform introduced in August 2015 regarding the Bankruptcy System. Despite this, the reform is minimal as to provide appropriate proposals and solutions to the underlying problems. Therefore, the bankruptcy system is not developed asa complete and efficient system for market agents.